Introduction to mathematical methods in physics - Fletcher, Glenn (Wm. C. Brown Publishers, 1994)
This concise, contemporary textbook is intended for a student's first course in mathematical methods for physics. Fletcher's approach of introducing and then applying mathematical methods to elementary problems in physics helps students learn the skills needed to continue with upper-level courses.